Lanthanide-based graded barrier structure for enhanced nanocrystal memory properties - Chan, T. K. (2012)
A memory structure comprising Ge nanocrystals and lanthanide-based charge trapping dielectric stack was fabricated to realize a self-aligned graded barrier structure. By exploiting efficient charge